2019
DOI: 10.1002/ncp.10267
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip Strength in Preoperative Elective Cardiac Surgery Patients and Association With Body Composition and Surgical Risk

Abstract: Background Handgrip strength (HGS) is a potential method to approximate perioperative risk in cardiothoracic surgery patients and correlates well with European System for Cardiac Operative Risk Evaluation (EuroSCORE) values. This study aimed to characterize the functional capacity in preoperative cardiac surgery patients through HGS. Methods This cross‐sectional study investigated patients aged 18 years or older. The collected data included surgical risk (EuroSCORE), body mass index (BMI), body composition (el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(74 reference statements)
2
8
0
Order By: Relevance
“…Since we may well infer from low HGS that PWV may be high-only 5.4% in the highest handgrip strength tertile had a high PWV > 11 m/s, compared to 39.4% in the lowest tertile-and measurement of HGS is done in a few seconds and inexpensive, it may be the ideal screening tool. In a similar vein, handgrip strength has been shown to correlate well with European System for Cardiac Operative Risk Evaluation (EuroSCORE) values 60 .…”
Section: Discussionmentioning
confidence: 84%
“…Since we may well infer from low HGS that PWV may be high-only 5.4% in the highest handgrip strength tertile had a high PWV > 11 m/s, compared to 39.4% in the lowest tertile-and measurement of HGS is done in a few seconds and inexpensive, it may be the ideal screening tool. In a similar vein, handgrip strength has been shown to correlate well with European System for Cardiac Operative Risk Evaluation (EuroSCORE) values 60 .…”
Section: Discussionmentioning
confidence: 84%
“…126 More recent studies, not addressed in the review, have evinced a relationship between grip strength and complications/post-operative risk in patients undergoing surgery for abdominal cancer 127 or elective cardiac surgery. 128 A contemporary study of patients hospitalized for hip fractures showed their grip strength to be associated with a risk of pressure ulcers. 129 The literature is inconsistent, but hospital and rehabilitation length of stay and readmission have been shown in several studies to correlate with grip strength.…”
Section: Grip Strength As a Biomarker Of Future Outcomesmentioning
confidence: 99%
“…Previous studies have also shown that HS was correlated with the severity of the disease, with aging and mortality in elderly individuals [15,16]. Particularly in cardiac surgery, HS has been well-recognized as a preoperative risk assessment tool since weak HS has been associated with 1-year and 30-day mortality, heart failure, kidney disease, malnutrition, and various frailty scales [17][18][19]. Hence, our study concurs with the growing body of literature regarding the poor outcomes of cardiac surgery patients with low preoperative PA and HS, and adds that their combined assessment might be an option to consider as a risk stratification tool.…”
Section: Discussionmentioning
confidence: 99%